Quality of reporting among systematic reviews underpinning the ESC/ACC guidelines on ventricular arrhythmias and sudden cardiac death. Issue 6 (11th March 2022) - Garrett, Elizabeth Payton; Hightower, Brooke; Walters, Corbin; Srouji, Derek; Chronister, Justin; Torgerson, Trevor; Hartwell, Micah; McIntire, Ryan; Love, Mitchell; Vassar, Matt
Abstract : Objectives: The main objective of this study was to assess the methodological and reporting quality of the systematic reviews (SRs) supporting the European Society of Cardiology (ESC) and the American College of Cardiology (ACC) clinical practice guidelines (CPGs) recommendations for the management of patients with ventricular arrhythmias and sudden cardiac death (SCD). As a secondary objective, we sought to determine: (1) the proportion of Cochrane SRs were cited; and (2) whether Cochrane SRs scored higher on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and A Measurement Tool to Assess Systematic Reviews 2 (AMSTAR-2) appraisals. Design: Cross-sectional analysis. Main outcome measures: We searched for CPGs published by the ESC and the ACC from 2010 to 2020. We selected the CPGs for ventricular arrhythmias and the prevention of SCD. The reference sections were searched for SRs. Two independent investigators evaluated eligible SR using the PRISMA checklist and the AMSTAR-2 assessment tool. Results: Two CPGs for ventricular arrhythmia and SCD were included in this study. Fifty-five SRs were included in our analysis. Across all SRs, the mean PRISMA score was 0.70. The lowest scoring PRISMA item related to the presence of a pre-published protocol (item 5, score 0.17). Overall, 40% of included SRs were found to have 'critically low' AMSTAR-2 ratings. One of the lowest scoring items for AMSTAR-2 was reporting of sources of funding (item 10). The 4 Cochrane SRs that were included scored higher on both assessment tools than non-Cochrane studies, specifically in PRISMA overall completion (88.7% vs 69.7%). Conclusion: Our study suggests the methodological and reporting quality of SRs used within ESC and ACC CPGs is insufficient, as demonstrated by the lack of adherence to both AMSTAR-2 and PRISMA checklists. Given the importance of CPGs on clinical decision making, and ultimately patient care, the methodological rigour and quality reporting within SRs used in CPGs should be held to the highest standard within the field of cardiology.